Analysis of thermo-magnetic convection and entropy generation of Al2O3-water nanofluid in a partially heated wavy electronic cabinet. (April 2022) - Sivaraj, C.; Gowtham, S.; Elango, M.; Sheremet, M.A.
Abstract: A computational analysis has been performed to study the effect of magnetic parameter on magneto-natural convection and entropy generation inside a wavy cabinet filled by Al 2 O 3 - H 2 O nanosuspension. The vertical boundaries of the cavity are designed as wavy and kept at cooled temperature ( T c ), while the horizontal borders are modeled as flat and supposed to be thermally insulated except the centrally heated portion on the bottom wall. The higher constant temperature ( T h ) of the isothermal line source can supply thermal energy in uniform manner. The transformed dimensionless governing equations were solved using finite volume technique along with power-law scheme. The system was optimized for significant variety of controlling parameters namely, number of undulations ( N  = 0–3), volume fraction of nanosuspension (ϕ = 0.0–0.04), magnetic parameter ( Ha  = 0 and 50), magnetic tilted angle (ζ = 0°–90°) and dimensionless heat difference (Ω = 0.001–0.1). The numerical results are analyzed for streamlines, isotherms, entropy isolines, overall Nusselt number and average entropy production strength. From this study, it is noticeable that growth of undulation number causes the reduction of convective heat transfer rate as well as average entropy production intensity. Further, the findings elucidate that the average entropy production intensity and overall heat transfer rate are decreased upon growing magnetic parameter.